Isolated ectopic jejunal varices in a patient with extrahepatic portal vein obstruction – A case report. (September 2021) - Solanki, Sanket; Jena, Suvendu Sekhar; Das, Sri Aurobindo Prasad; Yadav, Amitabh; Mehta, Naimish N.; Nundy, Samiran
Abstract: Introduction and importance: Among the various causes for lower gastrointestinal bleeding, ectopic varices constitute a small chunk. Though rare, these can pose a diagnostic challenge with recurrent bleed leading to multiple admission and blood transfusions. Case presentation: A 41-year-old male presented to our department with multiple episodes of melena. On further evaluation with CT angiography, a diagnosis of extrahepatic portal vein obstruction with moderate splenomegaly and ectopic jejunal varix was made. He underwent splenectomy with resection of involved jejunal segment with side to side anastomosis. Clinical discussion: The diagnosis of ectopic varices remains elusive in a large number of cases in view of the varied etiology. Various newer endoscopic and imaging modalities can play a diagnostic as well as therapeutic role but this also further complicates the management as there is a lack of substantial guidelines directing the treatment protocol. As a result, we have to resort to a case by case approach for the optimal management in these cases. Conclusion: The main modality of management for bleeding ectopic varices is percutaneous or endoscopic. Surgery is reserved for refractory cases, with decompressive shunts combined with segmental resection of involved intestine being at the forefront of surgical options. Highlights: Ectopic varices are an unusual cause of lower GI bleeding caused by porto-systemic collaterals. Ectopic varices most commonly occur at jejuno-ileum, but duodenal varices are more prone to bleed. The optimal management varies with each case due to paucity of treatment guidelines. Decompressive shunt with splenectomy and segmental resection of intestine effectively prevents rebleeding.